2016
DOI: 10.1016/j.scog.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Decoding emotion of the other differs among schizophrenia patients and schizoaffective patients: A pilot study

Abstract: The deficit in ability to attribute mental states such as thoughts, beliefs, and intentions of another person is a key component in the functional impairment of social cognition in schizophrenia. In the current study, we compared the ability of persons with first episode schizophrenia (FE-SZ) and individuals with schizophrenia displaying symptomatic remission (SZ-CR) to decode the mental state of others with healthy individuals and schizoaffective patients. In addition, we analyzed the effect of dopamine-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 47 publications
1
14
2
Order By: Relevance
“…Here, it was shown that both first episode and chronic schizophrenia patients performed worse in decoding negative and neutral emotional valances than the control group, yet no differences were observed in positive valence. 18 There is a consensus agreeing patients with schizophrenia have difficulties decoding the emotion perception of others, but there are two hypotheses regarding the nature of these deficits. The first is that the emotional perception impairment is secondary to generalized cognitive impairments, e.g., visuoperceptual ability.…”
Section: Discussionmentioning
confidence: 99%
“…Here, it was shown that both first episode and chronic schizophrenia patients performed worse in decoding negative and neutral emotional valances than the control group, yet no differences were observed in positive valence. 18 There is a consensus agreeing patients with schizophrenia have difficulties decoding the emotion perception of others, but there are two hypotheses regarding the nature of these deficits. The first is that the emotional perception impairment is secondary to generalized cognitive impairments, e.g., visuoperceptual ability.…”
Section: Discussionmentioning
confidence: 99%
“…Components of social cognition include emotion perception and regulation and “theory of mind,” or the ability to imagine the psychological states and experiences of others (Green et al, 2015). The small relevant literature is inconsistent, with some reports that schizoaffective disorder patients outperform those with schizophrenia on theory of mind tasks (Chen et al, 2012; Fiszdon et al, 2007; Tadmor et al, 2016). In contrast, other studies indicate no significant differences between groups in terms of theory of mind (Greig et al, 2004; Hooper et al, 2010) or emotion perception (Fiszdon et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…ToM dysfunctions, as characterized by laboratory tests, are thought to be a hallmark feature of schizophrenia [1][2][3][4][5], which is present before the onset of psychosis [6,7] and in the biological relatives of schizophrenia patients [8][9][10]. Therefore, ToM dysfunctions may be viewed as potential endophenotypes [11][12][13][14], although the results are not equivocal and straightforward [15][16][17][18][19][20]. On the other hand, several studies highlighted the relevance of ToM functions in clinical outcome, functional prognosis, and quality of life in schizophrenia [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there are no similar long-term investigations into ToM functions in schizophrenia. Based on previous results [11][12][13][14], we hypothesized that patients with schizophrenia will show similar or worse performances on the RMET at the follow-up testing session relative to the baseline values. In addition, we also used tests for executive functions, attention, and speed of information processing to compare social cognitive (RMET) and neurocognitive functions.…”
Section: Introductionmentioning
confidence: 99%